Patients’ and nurses’ perceptions on autonomy in nursing interventions - Lemonidou, Chryssoula; Panagiotou, A; Leino-Kilpi, Helena; Välimäki, Maritta; Dassen, Theo; Gasull, Maria; Scott, Philomena Anne; Arndt, Marianne; Merkouris, Anastasios (My University, 2003)
Aim: The investigation of patients' and nurses' perceptions on actualization of patients' autonomy in nursing interventions in maternity, surgical and elderly care. Material - Method: The sample consisted of 678 patients and 587 nurses/midwives from the corresponding wards. Two parallel questionnaires, developed by the researchers, were distributed for data collection. Results: Compared to nurses, patients perceived to receive less information (mean=2.34-3.13, p<0.001) and had fewer opportunities to make decisions regarding their care (mean=2.60-3.2L p<0.001). This difference was greater for personal hygiene, bladder and bowel function. Surgical patients perceived they have been given less information (mean=1.87, p<0.05) and opportunities to make decisions (mean =2.16, p<0.05) than mothers (mean=2.75-2.79, respectively) and elderly patients (mean=2.56-3.06 respectively). Nurses/midwives of postnatal wards perceived they have given information (mean=4.10, ρ<0.05) and opportunities for decision making to mothers (mean=3.64, p<0.05) more than the other two samples (surgical=3.37-2.84, elderly=3.3-3.16 respectively). Women, patients with planned admission and those who were asked to give informed consent perceived they have been given more information and opportunities to make decisions regarding their care. Conclusions: Study findings underline the problem of low actualization of patients in their autonomy and indicate the need of nurses/midwives basic and continuous education in subjects of clinical ethics in order to improve the ethical quality of nursing care.